Making the Most of the Host; Targeting the Autophagy Pathway Facilitates Staphylococcus aureus Intracellular Survival in Neutrophils - Vozza, Emilio G.; Mulcahy, Michelle E.; McLoughlin, Rachel M. (Frontiers in Immunology, 2021)
The success of Staphylococcus aureus as a human commensal and an opportunistic pathogen relies on its ability to adapt to several niches within the host. The innate immune response plays a key role in protecting the host against S. aureus infection; however, S. aureus adeptness at evading the innate immune system is indisputably evident. The “Trojan horse” theory has been postulated to describe a mechanism by which S. aureus takes advantage of phagocytes as a survival niche within the host to facilitate dissemination of S. aureus to secondary sites during systemic infection. Several studies have determined that S. aureus can parasitize both professional and non-professional phagocytes by manipulating the host autophagy pathway in order to create an intracellular survival niche. Neutrophils represent a critical cell type in S. aureus infection as demonstrated by the increased risk of infection among patients with congenital neutrophil disorders. However, S. aureus has been repeatedly shown to survive intracellularly within neutrophils with evidence now supporting a pathogenic role of host autophagy. By manipulating this pathway, S. aureus can also alter the apoptotic fate of the neutrophil and potentially skew other important signalling pathways for its own gain. Understanding these critical host-pathogen interactions could lead to the development of new host directed therapeutics for the treatment of S. aureus infection by removing its intracellular niche and restoring host bactericidal functions. This review discusses the current findings surrounding intracellular survival of S. aureus within neutrophils, the pathogenic role autophagy plays in this process and considers the therapeutic potential for targeting this immune evasion mechanism.